2019
DOI: 10.9789/2175-5361.2019.v11i4.998-1004
|View full text |Cite
|
Sign up to set email alerts
|

Taxi drivers’ mental health status and their life quality / Condições de saúde mental e qualidade de vida de taxistas

Abstract: Objetivos: Avaliar a influência das condições de saúde mental na Qualidade de Vida dos taxistas. Métodos: Estudo de corte transversal realizado com 133 taxistas associados ao Sindicato dos Condutores Autônomos de Jequié-Ba. Para avaliar a Qualidade de Vida foi utilizado o questionário Whoqol-Bref e o questionário SRQ-20 para as condições de saúde. Para as análises estatísticas foi utilizado o teste de Mann Whitney, adotando nível de confiança de 5% (p<0,05). A pesquisa teve aprovação do Comitê de Ética em P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Drivers with lower education levels reported more work-related accidents and lower quality of life [ 24 ]. Although in previous studies, drivers’ QOL was not significantly related to their level of education [ 28 , 29 ], the previous studies explicitly clarified the importance of education. They thus reported that the solution to the problems of reckless and aggressive behavior of taxi drivers is to teach them to pay attention to traffic laws and ways to deal with fatigue and reduce risky behaviors [ 3 , 7 , 30 ].…”
Section: Discussionmentioning
confidence: 88%
“…Drivers with lower education levels reported more work-related accidents and lower quality of life [ 24 ]. Although in previous studies, drivers’ QOL was not significantly related to their level of education [ 28 , 29 ], the previous studies explicitly clarified the importance of education. They thus reported that the solution to the problems of reckless and aggressive behavior of taxi drivers is to teach them to pay attention to traffic laws and ways to deal with fatigue and reduce risky behaviors [ 3 , 7 , 30 ].…”
Section: Discussionmentioning
confidence: 88%
“…Puesto que como indica De Souza «El trabajo duro desata problemas que influyen en la salud motora, produciendo además, fatiga intensa» (14) .…”
Section: Discussionunclassified
“…«Modelo de atención al Sistema de seguridad y salud en el lugar de trabajo para los conductores públicos urbanos en el área metropolitana de Guadalajara, México» (13) Deficientes, expuestos a contaminación, quemaduras solares, vibraciones, ruido, sobrecarga laboral ---------Falta un modelo de seguridad y salud en el trabajo para los conductores de transporte público «Condiciones de salud mental y calidad de vida de taxistas» (14) Expuestos a vibraciones, largos periodos de tiempo sentados, demora en el tráfico, trabajo exhaustivo…”
Section: Nombre Artículo Condiciones De Trabajo Estado De Salud Concl...unclassified
“…5 Research has identified specific mental health issues prevalent among drivers, such as stress and anxiety, 6 which may affect their driving quality, job satisfaction and overall well-being. 7 Many ORHDs start this job due to the burden of debt. 8 Previous research found that household financial debt can impact physical health by mediating healthcare behaviours and mental health.…”
Section: To the Editormentioning
confidence: 99%